Удoскoнaлeння мeхaнізмів дeржaвнoї підтримки рoзвитку мaлoгo підприємництва на регіональному рівні - Лізунков, Олександр Олександрович; Lizunkov, Oleksandr (ЦНТУ, 2024)
Метою написання кваліфікаційної роботи виступає дослідження рівня дeржaвнoї підтримки рoзвитку мaлoгo підприємництва в Кіровоградській області. Об’єктом дослідження є мале підприємництво в Кіровоградській області. Предметом кваліфікаційної роботи – теоретичні, методологічні та практичні аспекти державного регулювання розвитку малого підприємництва. The purpose of writing the thesis is to study the level of state support for the development of small businesses in the Kirovograd region. The object of the study is small businesses in the Kirovograd region. The subject of the thesis is theoretical, methodological and practical aspects of state regulation of the development of small businesses.
Improvement of mechanisms for state support of small business development at the regional level
Keywords: державна підтримка; мале підприємництво; бізнес; state support; small entrepreneurship; business